Development and simulation of the aqueous humor flow in the anterior chamber - Olkhovskiy, Vladislav; Friedmann, Elfriede (Conference "Topical Problems of Fluid Mechanics 2017", 2017)
We develop a mathematical model for the aqueous humor flow in the anterior chamber of a human eye. Therefore, we construct a two-dimensional geometry of the flow domain and consider the Stokes equation therein. Characteristics are the inflow, the production of the aqueous humor in the ciliary body, the path along the intraocular lens and the iris into the anterior chamber and the outow through the trabecular meshwork described by a porous media with the Darcy equations for the flow. We will present our first numerical simulations of the decoupled models on two separated domains, the anterior chamber and the trabecular meshwork.
Gesehen am 17.09.2018